2011
DOI: 10.1007/s11803-011-0082-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of friction dissipators for seismic protection of building structures

Abstract: This paper presents unidirectional shaking table tests of two reduced scale steel models of building frames; they have one and two floors, respectively. Such frames incorporate friction dissipators at every floor. The inputs are sine-dwells and artificial and registered earthquakes. This work belongs to a larger research project aiming to assess the seismic efficiency of friction dissipators by means of an integrated numerical and experimental approach. Inside this framework, the main objectives of these exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Additionally, they do not suffer from material yielding and repeated fatigue problems, which would necessitate their replacement after an earthquake, show no fluid leakage problems, are hardly affected by the ambient temperature, and have low susceptibility to deterioration over time. Various types of friction device have been proposed and developed, including translational motion devices, [4][5][6][7][8][9][10][11] rotational motion devices, [11][12][13] beam column joint devices, [14][15][16] and other devices. 9,17,18 The seismic response behavior of friction-damped (FD) systems has been experimentally investigated, [19][20][21] design methods and analytical studies have been reported, [22][23][24][25][26][27][28][29] and the installation of devices into actual building structures has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they do not suffer from material yielding and repeated fatigue problems, which would necessitate their replacement after an earthquake, show no fluid leakage problems, are hardly affected by the ambient temperature, and have low susceptibility to deterioration over time. Various types of friction device have been proposed and developed, including translational motion devices, [4][5][6][7][8][9][10][11] rotational motion devices, [11][12][13] beam column joint devices, [14][15][16] and other devices. 9,17,18 The seismic response behavior of friction-damped (FD) systems has been experimentally investigated, [19][20][21] design methods and analytical studies have been reported, [22][23][24][25][26][27][28][29] and the installation of devices into actual building structures has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…For most macroscopic modeling of friction dampers, the concept of Coulomb friction provides the theoretical basis, and the elastic‐perfectly plastic model is suitable for describing their force‐displacement relations as determined through physical testing results . Most of the frictional dampers are made of a set of metallic plates with a certain friction coefficient; the friction‐based devices yield at predetermined loads and provide dissipation of energy through friction during severe seismic excitations . The frictional damper exhibits stable hysteretic behavior under cyclic loads and a well‐defined sliding force by regulating normal forces acting perpendicularly to the friction surface …”
Section: Introductionmentioning
confidence: 99%
“…plates with a certain friction coefficient; the friction-based devices yield at predetermined loads and provide dissipation of energy through friction during severe seismic excitations. [15][16][17][18][19][20][21][22] The frictional damper exhibits stable hysteretic behavior under cyclic loads and a well-defined sliding force by regulating normal forces acting perpendicularly to the friction surface. [12,16,17] The force-deformation relation developed in a hysteretic damper is controlled by the initial stiffness and design slip-load or yield load.…”
mentioning
confidence: 99%
“…However, most of them are very expensive solutions, only suitable for special structural elements (tall buildings or very singular buildings). Therefore, they are not economically viable if massive use is intended in areas with low economic resources [1][2][3][4][5][6][7][8].Therefore, it is necessary to develop low-cost energy dissipation systems that are capable of being implemented in inexpensive precast concrete buildings without involving an unacceptable increase in the total cost of the building [9][10][11].Another common problem regarding the structural behavior of a building that had been subjected to an earthquake was that it was useless after the seismic event and, therefore, it had to be demolished. Regarding the situation of collapse during an earthquake, although it is a breakthrough, the economic cost for the community is still very high.…”
mentioning
confidence: 99%
“…However, most of them are very expensive solutions, only suitable for special structural elements (tall buildings or very singular buildings). Therefore, they are not economically viable if massive use is intended in areas with low economic resources [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%